Peningkatan Perilaku Pencegahan KEK (Kekurangan Energi Kronik) Pada Ibu Hamil: Increasing Behavior to Prevent CED (Chronic Energy Deficiency) in Pregnant Women - Indriyani, Ratna; Anggraini, Novita Anna (Jurnal Abdi Keperawatan dan Kedokteran, 2024)
Maternal and child health problems in Indonesia are an important issue in the health sector because of the high MMR. The purpose of the activity is to make an effort to improve KEK prevention behavior in pregnant women so that KEK prevention behavior can be carried out optimally at the Pasongsongan Health Center, Sumenep Regency. The activities carried out include counseling on KEK prevention behavior. Counseling is done by providing material about KEK and its dangers and how to prevent it. After the activity, an evaluation was conducted to determine the extent to which knowledge about KEK prevention had been captured by the participants. The results of preventive behavior of pregnant women before counseling found negative results, namely 48 pregnant women, while after counseling found negative results decreased to 35 pregnant women. For positive behavioral results before counseling there were 52 respondents, while after counseling it increased to 65 respondents. Evaluation is carried out to reveal errors or shortcomings in education about KEK prevention behavior in pregnant women. The results of distributing questionnaires before and after education showed an increase in the behavior of pregnant women from negative to positive. Educational activities on KEK prevention behavior can take place continuously and evaluate its implementation.